Empire of love : histories of France and the Pacific - Matsuda, Matt K. (Oxford University Press, 2005)
Presents multiple studies of the creation of an 'Empire of Love' in the Pacific and the interconnections between culture and imperial power in the nineteenth and twentieth centuries. This book examines the European presence in territories as Tahiti, New Caledonia, and Wallis and Futuna, and encounter and conflict in Panama, Indochina, and Japan.